Clinical, genetic, neurophysiological and functional study of new mutations in episodic ataxia type 1. Issue 10 (24th January 2013) - Tomlinson, Susan Elizabeth; Rajakulendran, Sanjeev; Tan, Stella Veronica; Graves, Tracey Dawn; Bamiou, Doris-Eva; Labrum, Robyn W; Burke, David; Sue, Carolyn M; Giunti, Paola; Schorge, Stephanie; Kullmann, Dimitri M; Hanna, Michael G
Abstract : Background and objective: Heterozygous mutations in KCNA1 cause episodic ataxia type 1 (EA1), an ion channel disorder characterised by brief paroxysms of cerebellar dysfunction and persistent neuromyotonia. This paper describes four previously unreported families with EA1, with the aim of understanding the phenotypic spectrum associated with different mutations. Methods: 15 affected individuals from four families underwent clinical, genetic and neurophysiological evaluation. The functional impact of new mutations identified in the KCNA1 gene was investigated with in vitro electrophysiology and immunocytochemistry. Results: Detailed clinical documentation, dating back to 1928 in one family, indicates that all patients manifested episodic ataxia of varying severity. Four subjects from three families reported hearing impairment, which has not previously been reported in association with EA1. New mutations (R167M, C185W and I407M) were identified in three out of the four families. When expressed in human embryonic kidney cells, all three new mutations resulted in a loss of Kv 1.1 channel function. The fourth family harboured a previously reported A242P mutation, which has not been previously described in association with ataxia. Conclusions: The genetic basis of EA1 in four families is established and this report presents the earliest documented case from 1928. All three new mutations caused a loss of Kv 1.1 channel function. The finding of deafness in four individuals raises the possibility of a link between Kv 1.1 dysfunction and hearing impairment. Our findings broaden the phenotypic range associated with mutations in KCNA1 .